Forest Provisioning Services of Chitwan National Park, Nepal - Pahadi, Rajbabu; Singh, Ombir; Pant, K. P.; Dahal, K. P. (Indian Forester, 2014)
To assess the provisioning services of CNP forest ecosystem, a questionnaire survey was conducted to know the quantity and value of non timer forest products (NTFPs) extracted from the CNP by the users of buffer zone community forests (BZCFs) during October 2012 to January 2013 in five selected BZCFs. The results showed that a total of 8275.19 tonne of biomass is extracted from the Chitwan National Park in the form of fuel - wood, fodder, grass, animal bedding, thatch / reed, fish, vegetables, medicinal plants and other NTFPs. Thatch/reed constitutes the highest quantity (48.88%) of the forest product to be extracted from the CNP followed by fuel wood (26.40%) and fodder/animal beddings (20.48%). The extraction of fish, vegetables, etc. constitutes about 2 % each of the total products. Total gross value of the forest products collected from the park is NRs (Napalese Rupee) 8,88,37000/ (888.37 lac) with a net value of NRs 4,12,16000/ (412.16 lac). The quantity of forest products extracted from the park has decreased over the years and this decrease in the extraction of forest resources could be attributed mainly to the establishment of BZCFs and the CNP has still to bear the demands of forest products of the local people.